Interactive Visualization Dashboard for Exploring Scientific Publications in Indonesia - Sihombing, Andre; Yaniasih,; Indrawati, Ariani; Afandi, Sjaeful; Ningsih Maha, Rahmadani (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Numerous bibliometric investigations have been carried out in Indonesia, primarily relying on publication data indexed exclusively in Scopus. This study aims to leverage scientific publication data from the Indonesian Scientific Journal Database (ISJD) by constructing an interactive visualization dashboard for the analysis of Indonesian scientific publications. This dashboard is expected to become an additional reference for researchers in the field of bibliometrics. The stages of making this dashboard consist of Identification of visualization needs referring to previous research; data feasibility check; data correction and update; data visualization; and evaluation to assess the correctness of the data and the resulting visualization. Evaluation results indicate that the dashboard's analysis system is functioning effectively, offering diverse analysis options. Nonetheless, the system has limitations related to data quality in ISJD, necessitating improvements in terms of completeness, appropriateness, and data updates. Future research will enhance the dashboard by incorporating citation analysis calculations to evaluate the performance of authors and journals.